Association between the intensity of statin therapy and physical activity 1 year after acute coronary syndrome: a multicentre prospective cohort study in Switzerland - David Nanchen; Stephan Windecker; Isabella Locatelli; Nicolas Rodondi; Lorenz Räber; David Carballo; Francois Mach; Olivier Muller; Baris Gencer; Christian M Matter; Roland Klingenberg; Thomas Lüscher; et al. (BMJ Open)
Objectives To assess the association between the intensity of statin therapy and the level of physical activity in patients 1 year after an acute coronary syndrome (ACS).Design Prospective cohort study from the Special Program University Medicine-Acute Coronary Syndromes.Setting Four university hospital centres in Switzerland.Participants 2274 patients with a main diagnosis of ACS between 2009 and 2017 who were available for a 1-year follow-up visit 1 year after hospital discharge.Outcome measures Self-reported physical activity was assessed with the International Physical Activity Questionnaire. The level of physical activity in metabolic equivalent-minutes per week (MET-min/week) was first stratified into sedentary and physically active categories and then analysed continuously among physically active patients. Analyses were performed using a propensity score weighting approach.Results One year after ACS, 1222 (53.7%) patients were on high-intensity statin therapy, 890 (39.1%) were on low/moderate-intensity statin therapy and 162 (7.1%) were not on statin therapy. Compared with non-statin users, low-/moderate-intensity statin users and high-intensity statin users were more likely to be physically active than sedentary, with a fully adjusted OR of 2.86 (95% CI 1.12 to 7.26) and 4.52 (95% CI 1.68 to 12.20), respectively. Among physically active patients, physical activity level was similar across all statin user categories, with median levels of 2792.5, 2712.0 and 2839.5 MET-min/week in non-statin, moderate/low-statin and high-statin users, respectively (p=0.307).Conclusions One year after ACS, neither low-/moderate-intensity nor high-intensity statin uses were associated with reduced self-reported physical activity compared with non-statin use. The concern that statin therapy may impair physical activity among ACS patients was not confirmed in this study.